2020
DOI: 10.1186/s12889-020-8281-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mother’s education on full immunization of children aged 12–23 months in Eritrea: population and health survey 2010 data analysis

Abstract: Background: Although vaccination coverage in Eritrea has improved in recent years, some children are still missing out, and it's important to identify risk factors for lower coverage in order to target campaigns and interventions. The objective of this study was to assess: (1) the impact of maternal education on full immunization of children aged 12-23 months, and (2) whether the association was confounded or modified by other factors. Methods: This study was a secondary data analysis of the Eritrean Populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 15 publications
(21 reference statements)
3
19
2
2
Order By: Relevance
“…The potential variables associated with full childhood immunization were categorized as individual-and community-level variables. These variables have been selected based on different works of literature [12][13][14][15][16][17][18]. The individual-level variables include the age of mothers, wealth index, mothers employment status, maternal education level, father education level, number of living children, ANC visits during pregnancy, place of delivery, sex of household head, and PNC visit.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential variables associated with full childhood immunization were categorized as individual-and community-level variables. These variables have been selected based on different works of literature [12][13][14][15][16][17][18]. The individual-level variables include the age of mothers, wealth index, mothers employment status, maternal education level, father education level, number of living children, ANC visits during pregnancy, place of delivery, sex of household head, and PNC visit.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Previous studies conducted in various sub-Saharan African countries to identify factors related to full childhood immunization have been institutional-based and to consider only individual factors [12][13][14][15][16][17][18]. Nevertheless, childhood vaccination may be impacted by communitylevel factors such as media exposure [19,20], distance to health facilities [21,22], residence [23], country [24], and cluster (enumeration area) [24].…”
Section: Introductionmentioning
confidence: 99%
“…They found that 82.8% children of working mothers were completely immunized as against 83.4% children of nonworking mothers. The difference was not significant enough [51]. Using data of a Government General Hospital in India, [52] also didn't find significant difference between the immunization status of children of unemployed and employed mothers, though in this case the percentage of complete immunization among children of employed mothers were slightly higher.…”
Section: Discussionmentioning
confidence: 95%
“…11 Another population based study conducted in Eritrea demonstrated that mothers who attended primary level of education were more likely to have their children fully vaccinated than mothers who have not received any education. 12 A study conducted in Norway found out that HPV vaccine initiation increased with increasing maternal income. Also, HPV vaccination initiation was higher among girls with mothers of low education.…”
Section: The Following Are Among the Factors That Influencing Childhood Vaccine Uptakementioning
confidence: 99%